Fading and interference mitigation in wireless communications - Panic, Stefan R.; Stefanovic, Mihajlo; Anastasov, Jelena; Spalevic, Petar (Taylor & Francis, 2014)
Preface Professional bodies of note for electrical engineers, such as IET and IEEE, have over 500,000 members worldwide and hold over 3,000 conferences annually. Many of the members of these bodies are interested in advanced digital telecommunications and signal processing. According to latest statistical figures, the United States produces 50,000 electrical engineers in a year as against 70,000 by India and 100,000 by China. Digital telecommunications and signal processing are mandatory subjects at most of the faculties and colleges in these countries. Considering these facts, this book could present itself as a useful literature for introducing some basic principles of digital communications and its mathematical formalization and also for staying updated with the recent developments in the performance analysis of space diversity reception over fading channels in the presence of CCI. Researchers have been studying problems associated with these domains for more than 40 years, and system engineers have used the theoretical and numerical results reported in the literature to guide the design of their systems. In recent years, applications have become increasingly sophisticated, thereby requiring more complex models and improved diversity techniques along with the need to provide performance analyses of the scenarios studied. The primary goal of this book is to present a unified method to provide a set of tools that will allow the system designer to compute--